Keberadaan Keputusan Majelis Utama Desa Pakraman Bali (MUDP) Bali No. 01/Kep/Psm-3/MDP Bali/X/2010 di Desa Adat Lambing - Gusti Ayu Dewi Irna Yanthi; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Interpretasi Hukum, 2021)
Inheritance in Bali adheres to the Patrilineal principle where men have the right to inherit while women do not have the right to inherit. However, the Main Council of Pakraman Village (MUDP) Bali made a new breakthrough in which Balinese women can inherit. The purpose of this study is to describe the position of women's inheritance rights based on customary inheritance law in Bali and to describe the existence of the Bali Pakraman Village Main Council Decree (MUDP) No.01 / Kep / Psm-3 / MDP Bali / X / 2010 in Lambing Traditional Village. This study used an empirical research method by presenting data qualitatively. The results of the study stated that in the awig-awig of the traditional village of Lambing, the position of women was not as heirs. Meanwhile, the implementation of the decision of Pesamuhan Agung III of the Main Assembly of Pakraman Village has not been fully implemented. Lack of socialization and the enactment of awig-awig as a binding rule have resulted in the inability to implement this decision.